La renta ambiental de los bosques - Campos Palacín, P.; Caparrós Gass, A. (ARBOR Ciencia, Pensamiento y Cultura, 2008)
The objective of this paper is to show the measurement of the environmental income from two private Spanish forests, the Cork Oak Woodlands of the Alcornocales Natural Park (Cádiz and Málaga) and the Scotch Pine Forest of the Sierra de Guadarrama (Madrid and Segovia). We also contribute to the technical and political debate on governmental regulations of forest environmental accounting in European Union. We have measured the environmental goods and services consumed by private landowners and public visitors through the contingent valuation technique. We have estimated the value of mushrooms gathering by public visitors in the Scotch Pine Forests of the Sierra de Guadarrama taking the price and harvest from the mushroom market in Pinar Grande (Soria). The value for carbon estimated accounts for the avoided damage of the greenhouse effect mitigation due to the sequestration of the atmospheric carbon dioxide. The environmental valuations show that the private environmental profitability rates in the Alcornocales Natural Park and in the Sierra de Guadarrama are 2.13 % and 3.43 %, in relation to their corresponding land market prices. We have estimated that the total net values added are 1.63 and 3.28 times higher than its corresponding conventional net values added in the Alcornocales Natural Park and in the Sierra de Guadarrama.
Keywords: consumer surplus; Cork oak; Exchange value; Hicksian income; joint production; public expenditure; Scotch pine